Meliorating microcirculatory with melatonin in rat model of spinal cord injury using laser Doppler flowmetry. Issue 17 (7th December 2016) - Jing, Yingli; Bai, Fan; Chen, Hui; Dong, Hao
Abstract : The aim of this study was to estimate the effect of melatonin on spinal cord perfusion, the permeability of blood–spinal cord barrier (BSCB), and edema at the contusion epicenter and regions rostral and caudal to the injury site in rats with spinal cord injury (SCI). Thirty-six female Sprague–Dawley rats were divided into three groups (12 animals in each group): sham, SCI, and melatonin groups. Melatonin (50 mg/kg) was injected intraperitoneally at 30 min after a moderate injury at T10 in the melatonin group (twice a day). At 24 h postinjury, spinal cord perfusion was estimated using laser Doppler flowmetry, the permeability of BSCB was detected by Evan's blue, and edema was estimated by calculating the water content. A linear regression analysis was performed to assess the correlation between spinal cord perfusion and the permeability of BSCB or water content. Our results showed that melatonin significantly upregulated spinal cord blood flow and oxygen saturation in SCI rats using laser Doppler perfusion monitoring. Simultaneously, laser Doppler perfusion imaging indicated that melatonin markedly meliorated spinal cord perfusion in regions rostral and caudal to the injury site, rather than the epicenter site. Consistent with the results of laser Doppler flowmetry, melatonin significantly reduced the amount of Evan's blue dye and water content in regions of rostral and caudal cords. In addition, perfusion correlated with the permeability of BSCB and water content. These findings indicated that melatonin might exert a protective effect by meliorating microcirculation, which coordinated a corresponding response in the integrity of BSCB and edema.